2006
DOI: 10.1074/jbc.m506123200
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Sortase A Transpeptidase

Abstract: Many virulence factors in GramSurface proteins on bacteria are frequently virulence factors, promoting bacterial adhesion, resistance to phagocytic killing, and host cell invasion during infection. In Gram-positive bacteria these proteins are often covalently anchored to the cell wall by sortase enzymes, a family of novel cysteine transpeptidases (1-3). The sortase A protein (SrtA) 2 from Staphylococcus aureus has been characterized extensively (4) and anchors proteins bearing a cell wall sorting signal that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(97 citation statements)
references
References 65 publications
4
90
1
2
Order By: Relevance
“…This is consistent with an induced-fit mechanism. However, the observed fluctuations of the b6/ b7 loop between open and semi-closed states, and the previously reported NMR data on micro to millisecond timescale dynamics of these same residues, 30 point toward a conformational selection mechanism. Taken together, experiments and simulations therefore suggest a recognition model of conformational selection followed by induced fit, consistent with the emerging paradigm for a diverse range of recognition processes.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…This is consistent with an induced-fit mechanism. However, the observed fluctuations of the b6/ b7 loop between open and semi-closed states, and the previously reported NMR data on micro to millisecond timescale dynamics of these same residues, 30 point toward a conformational selection mechanism. Taken together, experiments and simulations therefore suggest a recognition model of conformational selection followed by induced fit, consistent with the emerging paradigm for a diverse range of recognition processes.…”
Section: Discussionmentioning
confidence: 64%
“…20 Because it has been shown to be important for the catalytic activity of the enzyme, a calcium ion was added to the structure, positioned in its known binding site. 20,30 Initial coordinates for the holo SrtA simulations were generated from the 2KID NMR structure in which an LPAT analog is covalently attached to the catalytic C184 residue in the enzyme's active site. 21 For the holo structure, an unmodified LPATG sequence was subsequently docked into this site using Glide with the XP scoring function, 42 and the structure in which the positions of the L, P, and A residues most closely matched those in the NMR structure was chosen for simulation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent NMR analyses by Naik et al (38) revealed that the backbone dynamics of the ␤6/␤7 loop in SrtA change significantly upon calcium binding. 15 Engineering the Substrate Specificity of S. aureus SrtA used the NPQTN-containing peptide Abz-KVENPQTNAGTDap(DNP)-NH 2 .…”
Section: Motifmentioning
confidence: 99%
“…In addition to providing the first molecular structure of a sortase enzyme (18), NMR has also been used to probe the dynamics of Sa-SrtA and determine the overall binding orientation of the sorting signal peptide to the protein (24,25). These studies revealed that Ca 2ϩ acts as an allosteric activator by stabilizing the structure of the ␤ 6 /␤ 7 loop in Sa-SrtA in a closed, substrate binding state and that the binding site for the LPXTGsorting signal comprises residues from ␤ 4 and␤ 7 and the ␤ 3 /␤ 4 and ␤ 6 /␤ 7 loops.…”
mentioning
confidence: 99%